Pedagogical English Proficiency Requirements for Elementary EFL Teachers - Ainun Zakiyah; Muhammad Hifdil Islam; Zainuddin Zainuddin (Universitas Galuh, 2026)
English proficiency plays a crucial role in supporting effective English as a Foreign Language (EFL) instruction at the elementary school level. However, in many elementary schools, English is taught by teachers whose educational backgrounds are not specifically related to English education and whose levels of English proficiency vary considerably. This study aimed to explore the English proficiency requirements needed by elementary school teachers in conducting EFL teaching and to examine how these competencies are manifested in instructional and interactional classroom practices at SDN Sindetanyar. The study was conducted to provide a deeper understanding of the competencies required for effective EFL instruction in elementary school contexts and the challenges associated with their implementation. Employing a qualitative case study design, data were collected through semi-structured interviews with three teachers who were purposively selected because they were responsible for teaching English in grades four, five, and six, complemented by classroom observations and document analysis. The data were analyzed using Saldaña’s first-cycle and second-cycle coding procedures. The findings revealed five key English proficiency requirements: instructional language, interactional competence, pronunciation, vocabulary explanation and simplification skills, and bilingual communication competence. The study also identified a discrepancy between teachers’ perceived understanding of these competencies and their actual classroom enactment. The findings suggest that teacher proficiency should be understood as the interaction of professional knowledge, pedagogical enactment, and contextual support within elementary EFL settings.